On the Divergence of Voiced Lateral Approximants in Indo-European languages - G. M. Telezhko (Дискурс)
Introduction. This article is based on the results of a comparison of a number of Serbo-Croatian/Slovenian lexemes with a palatal lateral approximant [ʎ] and Western Slavic lexemes with a velarized lateral approximant [ɫ] with related lexemes in Slavic and other Indo-European (IE) languages. It is shown that the Balkan-Slavic [ʎ] irregularly corresponds to the phonemes [l'] and [j] of other Slavic languages and even some IE languages beyond the Slavic group. It is also shown that the West Slavic [ɫ] irregularly corresponds to the phonemes [l] and [w]/[v] of other Slavic and IE languages. Because of this irregularity, these phonetic correspondences are difficult to explain with local dialect features.Methodology and sources. A model based on the generalization of instrumental studies that showed that palatal sounds are characterized by instability of articulation is proposed. This leads to their divergent evolution, transformation into sounds with different stable zones of articulation.In the proposed model, the Proto-Indo-European (PIE) voiced lateral approximants *[ɫ] and *[ʎ], forming the opposition "hard consonant - soft consonant", in the process of phonetic evolution in IE languages were split into variants with a clearer articulation: velarized *[ɫ] > solid alveolar lateral [l] and bilabial fricative [w]; palatal *[ʎ] > soft alveolar lateral [l'] and palatal approximant [j]. Besides, the original consonants have survived in a number of languages.Results and discussion. Examples of correspondences are given to suggest the presence of *[ɫ] and *[ʎ] in PIE and Common Slavic prototypes. The newly discovered etymological links, such as the links between Russian lexemes баня 'bath' and балий, бальник 'healer, sorcerer' are being discussed.Conclusion. With the help of the mechanism of divergent evolution of the palatal lateral approximant *[ʎ] and the velarized lateral approximant *[ɫ] the irregularity of phonetic correspondences of voiced lateral approximants in Slavic languages can be uniformly explained.Besides, the acceptance of *[ʎ] and *[ɫ] in PIE phonology also lets us to establish some previously undetected etymological relations.